Economics and the Survivor Peasant - Flavio Pinto (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Peasants are survivor actors: they allocate all their resources and deploy refined strategies for securing a smooth horizon of consumption. Their stylized behavior is irrational only if development is the goal the peasant should follow. Subsistence as expression for describing rural economies is inadequate, since it doesn't connote the risk of starvation or death that peasants face. The survivor actor poses descriptive demands and normative implications. At a descriptive level, peasant's risk behavior is not ruled by inner preferences only, but depends on his expectations for securing a smooth consumption during the crop cycle. The utility model is apt for describing the survivor actor. Yet the exponent that defines the curvature of the utility includes a component that captures the aversion to uncertainty and a component that grasps the expectations about the chances to secure the horizon of consumption. This component defines a function of risk behavior, a counterpart of the Arrows-Pratt function of risk aversion. A normative for the survivor actor has to consider what is feasible, not what is desirable; what could be, not what should be.
Keywords: 330